Role of Polychronicity in Job Performance and Turnover Intention Mediated by Job Satisfaction and Work Engagement - Muhammad Donal Mon; Tan Wan I.; Antony Sentoso (Binus Business Review, 2025)
The research aimed to examine the mediating role of job satisfaction and work engagement in the relationships between polychronicity, job performance, and turnover intention among employees in Batam’s manufacturing industry. While polychronicity had been widely studied in service sectors, its impact within the structured, efficiency-driven manufacturing environment remained underexplored. The research filled this gap by examining how polychronicity influenced job outcomes in a sector that prioritized operational consistency and productivity. The research collected data from 350 manufacturing employees using a quantitative approach and purposive sampling. Then, data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS version 3.2.9 software. The findings reveal that polychronicity significantly influences job satisfaction, turnover intention, and work engagement but does not have a significant direct effect on job performance. Furthermore, job satisfaction and work engagement positively impact job performance, although they do not significantly affect turnover intention. The research also highlights the mediating roles of work engagement and job satisfaction between polychronicity and both job performance and turnover intention. However, work engagement does not mediate the relationship between polychronicity and turnover intention. These insights contribute to a nuanced understanding of how multitasking capabilities shape work outcomes under the unique pressures of manufacturing, emphasizing that demographic factors like gender, age, and marital status may further influence the effects of polychronicity